World Social Summit : ten benchmark issues (2000)
Focuses on the highlights of the ten major issues defined by, Social Watch in its 'Geneva Benchmark' document issued in 1999. Presents an assessment of the agreements reached by the Geneva Summit against the demands set out in the 'benchmark' document.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT